Implementasi Tawakal terhadap Gangguan Kecemasan pada Lansia di Desa Sanggi Kecamatan Bandar Negeri Semuong - Melia Santi; Andi Eka Putra; Nesia Mu’asyara (Pusat Riset dan Inovasi Nasional, 2024)
This research is motivated by the phenomenon of anxiety disorders experienced by some elderly in sanggi village, bandar negeri semuong sub-district, especially those caused by feelings of fear in themselves. This condition often arises from feelings of lack of support and attention from their families tend to experience feelings of anxiety that will have an impact on health. The method used is qualitative descriptivewith data collection through pbservation, in-depth interviews, and questionnaires. Participants were selected using purposive sampling based on the criteria for anxiety disorders in the elderly. The results of the study show that the implementation of tawakal is not only an expression to entrust everything to Allah SWT. But forms full trust and acceptance of what has been submitted. Elderly people who internalize tawakal tend to be more able to accept and surrender to Allah SWT, reduce feelings of worry, fear and build a positive view of what has happened. Implementation of tawakal strengthens inner peace, increases a sense of security, and motivates to improve the world as a whole. This finding confirms that the implementation of tawakal is an effective spiritual approach to overcome anxiety disorders.